Workshop of Composing Higher Order Thinking Skill Questions to Improve Pedagogy of Chemistry Teachers in Pesisir Selatan District - Zonalia Fitriza; Andromeda Andromeda; Faizah Qurrata Aini (Fakultas MIPA Universitas Negeri Padang, 2021)
Chemistry Teacher association of Pesisir Selatan district needs a workhop regarding to develop HOTS intrument since they still questioning the correct way to do HOTS evaluation. Therefore, community service team of Chemistry Department conducted a workshop to improve pedagogy competency particularly in HOTS evaluation. This workhop was implemented via zoom meeting by giving explanation about evaluation and revised Bloom Taxonomy for knowledge domain. It continued workshop to develop HOTS evaluation that started by interpreting Basic Competences (BC) to competence achivement indicator (CAI), the CAI to HOTS question indicators and develop the HOTS question through on job learning. The team assessed the result and discussed it with the teachers. They revised the mistakes and the team compile it to be the HOTS question bank. As an evaluation, the teachers fill the questionnaires about the online workshop